Novel variant in HHAT as a cause of different sex development with partial gonadal dysgenesis associated with microcephaly, eye defects, and distal phalangeal hypoplasia of both thumbs: Case report - Baz-Redón, Noelia; Soler-Colomer, Laura; Fernández-Cancio, Mónica; Benito-Sanz, Sara; Garrido, Marta; Moliné, Teresa; Clemente, María; Camats-Tarruella, Núria; Yeste, Diego (Frontiers in Endocrinology, 2022)
The palmitoylation of the Hedgehog (Hh) family of morphogens, named sonic hedgehog (SHH), desert hedgehog (DHH), and Indian hedgehog (IHH), is crucial for effective short- and long-range signaling. The hedgehog acyltransferase (HHAT) attaches the palmitate molecule to the Hh; therefore, variants in HHAT cause a broad spectrum of phenotypes. A missense HHAT novel variant c.1001T>A/p.(Met334Lys) was described in a patient first referred for a 46,XY different sexual development with partial gonadal dysgenesis but with microcephaly, eye defects, and distal phalangeal hypoplasia of both thumbs. The in silico analysis of the variant predicted an affectation of the nearest splicing site. Thus, in vitro minigene studies were carried out, which demonstrated that the variant does not affect the splicing. Subsequent protein in silico studies supported the pathogenicity of the variant, and, in conclusion, this was considered the cause of the patient’s phenotype.